Model Matematika Pengaruh Lingkungan Terhadap Bertambahnya Pengkonsumsi Alkohol - Bayu Kurnia Putra; Media Rosha; Dewi Murni (UNIVERSITAS NEGERI PADANG, 2021)
Abstract – In this article discussed the mathematical model increacing influence of environment on consuming alcohol. This research was started by forming mathematical model increacing influence of environment on consuming alcohol in the of non-linear differential equations system. From the analysis mathematical model increacing influence of environment on consuming alcohol, there are two types of equilibrium point. Free equilibrium point of consuming alcohol and equilibrium point of consuming alcohol. Terms existence and stability of the equilibrium point is determined by the basic reproduction number. By analyzing the model, obtained the stability of each equilibrium pointsKeywords – Mathematical Model, Alcohol, Equilibrium, Stability, Basic Reproductive Number